Hubungan Sanitasi Total Berbasis Masyarakat (STBM) terhadap Kejadian Stunting Pada Balita Usia 0-59 Bulan - Puspitasari, Rini Dwi; Rahayuwati, Laili; Khoirunnisa, Khoirunnisa; Juniarti, Neti; Mardiah, Wiwi (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Sanitation as an indirect risk factor for stunting needs to be considered because it plays a role in influencing and minimizing the deterioration of health status due to the main factors that cause stunting: nutritional deficiencies and infectious diseases is needed. Good sanitation can be realized by implementing the STBM program according to government recommendations. This study aims to see the relationship between the implementation of STBM and the incidence of stunting in toddlers. This study uses a correlational descriptive research design with a cross-sectional approach. The sample was selected using a total sampling technique of 96 parents who have children under five in Sukamulya Village. Data analysis used the chi-square correlation test. The results showed there was no relationship between the implementation of Community-Based Total Sanitation (STBM) and the incidence of stunting in toddlers. Whether the implementation of STBM is good or bad does not affect the incidence of stunting in toddlers. The stunting incident found in Sukamulya Village, Rancaekek District, Bandung Regency is included in the stunting event group that is not affected by the STBM implementation